The impact of additive or substitutive clinical study design on the negotiated reimbursement for oncology pharmaceuticals after early benefit assessment in Germany - C. M. Dintsios; I. Beinhauer (Health Economics Review, 2020)
Background: We analysed the impact of clinical study design for oncological pharmaceuticals on the subsequent price negotiations after early benefit assessment between pharmaceutical companies and the German National Association of Statutory Health Insurance Funds. The analysis was conducted for all oncology pharmaceuticals that underwent the early benefit assessment in Germany since its introduction in 2011 up to September 2016. Methods: It was differentiated between additive (new therapy in addition to baseline therapy) and substitutive study designs (baseline therapy to be replaced). The study design was derived from the dossiers of the pharmaceutical companies submitted to the Federal Joint Committee. Subgroup specific costs in case of granted added benefit were calculated as annual therapy costs and compared with the costs of the appropriate comparators to quantify price premiums. Further price influencing factors were analysed in univariate and multivariate regression analysis considering the budget impact for the statutory health insurance as well. Results: The mean and the median of the additive premiums for substitutive designs ( exteuro50,477.68 and exteuro49,841.24) were higher than for additive designs, if the comparator was different to best supportive care ( exteuro48,750.00 and exteuro42,820.44). The mean multiplicative premium for the substitutive designs was 15.07 versus 2.29 for the additive designs. EU-Prices and target population size had a significant effect on the reimbursement. The adjusted R-square in the log Premium OLS-regressions reached 0.708 when including all explanatory variables and considering interaction between target population and annual costs of the comparator.Conclusions: Study design as an additional important influencing factor of the negotiations next to those stated in the framework agreement was identified and verified. Therefore, study design should be considered by pharmaceutical companies and by decision makers and payers within strategic price planning as a potential predictor. For some specific categories the number of cases was small. Further analyses should be performed when more oncology pharmaceuticals have passed the early benefit assessment.
Keywords: I11; I13; I18; 330; Study desig; Negotiated prices; Oncological drugs; Pharmaceutical companies; Payers; German statutory health insurance